Remote sensing and in situ measurements of methane and ammonia emissions from a megacity dairy complex: Chino, CA. (February 2017) - Leifer, Ira; Melton, Christopher; Tratt, David M.; Buckland, Kerry N.; Clarisse, Lieven; Coheur, Pierre; Frash, Jason; Gupta, Manish; Johnson, Patrick D.; Leen, J. Brian; Van Damme, Martin; Whitburn, Simon; et al.
Abstract: Methane (CH4 ) and ammonia (NH3 ) directly and indirectly affect the atmospheric radiative balance with the latter leading to aerosol generation. Both have important spectral features in the Thermal InfraRed (TIR) that can be studied by remote sensing, with NH3 allowing discrimination of husbandry from other CH4 sources. Airborne hyperspectral imagery was collected for the Chino Dairy Complex in the Los Angeles Basin as well as in situ CH4, carbon dioxide (CO2 ) and NH3 data. TIR data showed good spatial agreement with in situ measurements and showed significant emissions heterogeneity between dairies. Airborne remote sensing mapped plume transport for ∼20 km downwind, documenting topographic effects on plume advection. Repeated multiple gas in situ measurements showed that emissions were persistent on half-year timescales. Inversion of one dairy plume found annual emissions of 4.1 × 10 5 kg CH4, 2.2 × 10 5 kg NH3, and 2.3 × 10 7 kg CO2, suggesting 2300, 4000, and 2100 head of cattle, respectively, and Chino Dairy Complex emissions of 42 Gg CH4 and 8.4 Gg NH3 implying ∼200k cows, ∼30% more than Peischl et al. (2013) estimated for June 2010. Far-field data showed chemical conversion and/or deposition of Chino NH3 occurs within the confines of the Los Angeles Basin on a four to six h timescale, faster than most published rates, and likely from higher Los Angeles oxidant loads. Satellite observations from 2011 to 2014 confirmed that observed in situ transport patterns were representative and suggests much of the Chino Dairy Complex emissions are driven towards eastern Orange County, with a lesser amount transported to Palm Springs, CA. Given interest in mitigating husbandry health impacts from air pollution emissions, this study highlights how satellite observations can be leveraged to understand exposure and how multiple gas in situ emissions studies can inform on best practices given that emissions reduction of one gas could increase those of others. Graphical abstract: On surface: Map of IASI ammonia, NH3, columns for the Eastern Los Angeles Basin for 2014.Floating: Mako NH3 column map. Surface shows pink outline of the Chino Diary Complex, grey outlines 70 ppm-m contour of NH3 column. IASI map slightly transparent to provide better surface rendering. The excellent spatial agreement indicates that conditions for Mako were typical. Highlights: Airborne remote sense mapping of a dairy trace gas plume for over 20 km. In situ identification of far-field (70-km) downwind plume by surface in situ and satellite. Good herd size agreement for a dairy and the Chino Dairy Complex based on multiple gas emissions estimates. NH3 lifetime was rapid, ∼6 h, likely due to increased oxidation from the higher oxidant loads in Los Angeles. IASI satellite NH3 and CH4 confirmed downwind plume and transport patterns identified in airborne imaging spectroscopy and surface in situ data. Abstract : Airborne remote sensing mapped dairy NH3 and CH4 plumes with good agreement with satellite and in situ data, the latter of which were used to derive emissions and infer herd size.